Collaborative Strategies for Developing an Arabic Language Curriculum Incorporating Bugis Local Wisdom - Awaluddin, A. Fajar; Ridwan; Riskianti, Arvina Windah; Rezki, Rezki (Prodi Manajemen Pendidikan Islam Pascasarjana Institut Pesantren KH. Abdul Chalim Mojokerto, 2024)
Although many studies have examined inter-university collaboration in developing Arabic language curricula, research incorporating Bugis local wisdom in Islamic universities remains limited. Therefore, this study aims to identify collaboration strategies between universities in creating an Arabic language curriculum based on Bugis local wisdom in Arabic language courses and to design a theoretical framework that integrates Bugis local wisdom values. This research employs a qualitative approach, with participants consisting of Arabic language lecturers from collaborating universities, namely IAIN Bone and STAI Al-Gazali Bone. Data will be collected through literature reviews, observations, interviews, and document analysis. The research findings indicate that the implementation of inter-university collaboration in developing an Arabic language curriculum based on Bugis local wisdom involves five key stages: (1) identifying common goals, (2) forming a working team, (3) curriculum development, (4) learning material development, and (5) testing and evaluation. Meanwhile, the model for collaborative Arabic language curriculum development in higher education, integrated with Bugis local wisdom values, can be designed by considering the following principles: (1) identifying relevant Bugis local wisdom values, (2) consulting and collaborating with local stakeholders, and (3) preparing an integrated learning plan. This study has implications for improving the quality of Arabic language education, developing interdisciplinary competencies, and enhancing teaching materials and educational resources based on local wisdom.